ANALISIS YURIDIS PENGHENTIAN PENYIDIKAN KASUS PERSETUBUHAN PADA ANAK DALAM KELUARGA DENGAN ALASAN MEDIASI BERDASARKAN HUKUM PIDANA INDONESIA - Yuli Shara Sihombing; Evi Deliana; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
One form of crime that occurs in the community, namely sexual intercourse is regulated in the Criminal Code, namely Article 287 of the Criminal Code. Furthermore, the crime of sexual intercourse occurring in the family environment involving children as victims is known as cases of sexual intercourse with children in the family as regulated in Article 76 D and 76 E of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. Cases of sexual intercourse in the family are often not processed legally, one of which is the termination of the investigation or called SP-3 by the police due to mediation. Termination of the investigation on the grounds of mediation is not regulated in Article 109 paragraph (2) of the Criminal Procedure Code. Mediation is regulated at the level under the Act, namely in the Letter of the Chief of Police No. Pol: B/3022/XII/2009/SDEOPS dated December 14, 2009 regarding Case handling through Alternative Dispute Resolution (ADR) (police chief's letter 8/2009).Mediation arrangements in the police only apply to cases that cause small material losses and minor crimes, while cases of sexual intercourse with children in the family are ordinary offenses that cannot be resolved by mediation. The case was a serious crime and suffered considerable losses both physically and psychologically.This research will be structured using the type of normative juridical research, namely research that is focused on examining the application of legal rules or norms to legal principles and theories. The data collection technique used in this research is literature study. The approach used in this research is to use a normative approach, namely library law research.The results of the research conducted by the author are first, the provisions of the criminal law of mediation on the crime of sexual intercourse with children in the family are not regulated in Indonesian criminal law. based on the benchmark and scope of the case, it cannot be resolved by mediation. Second, the termination of the investigation of cases of sexual intercourse with children in the family on the grounds of mediation based on Indonesian criminal law in accordance with Article 109 paragraph (2) of the Criminal Procedure Code cannot be carried out because the Criminal Procedure Code has limited the reasons for the termination of the investigation. Even though the victim has made peace, the investigator is still obliged to process the case. The amicable agreement is only used as a consideration by the Prosecutor to reduce the maximum amount of his demands and the judge's consideration to reduce the sentence in the trial process in court.Keywords: Termination of Investigation - Sexual intercourse with children in the family – mediation